Synthesis and Characterization of Ferrihydrite Nanoparticles - Saini, Preeti (My University, 2014)
Undoped and nickel doped ferrihydrite nanoparticles are prepared by chemical routes. The samples are characterized by x-ray diffractometer, thermogravimetric analyzer and vibrating sample magnetometer. The average crystallite size is found to be about 2 nm. The prepared nanoparticles of undoped and nickel doped ferrihydrite are found to be antiferromagnetic at room temperature.
MS, SPMS
Keywords: Magnetic Nanoparticles; Superparamagnetism